Terapi Lintah Perspektif Hukum Islam dan Relevansinya Terhadap MaqᾹṣid Al-Syarī’ah - Rosmita, Rosmita; Mahmuddin, Ronny; Aisyiah, Nurul; Nasaruddin, Nasaruddin (Islamadina : Jurnal Pemikiran Islam, 2024)
This study aims to determine the leech therapy perspective of Islamic law and its relevance to MaqÄá¹£id al-SyarÄ«’ah. This research uses the library research method with historical and juridical-normative approaches. The results of this study indicate that treatment with leech therapy from the perspective of Islamic law and MaqÄá¹£id al-SyarÄ«’ah is permissible. Characteristics of this animal (leech) can be found on land and in water so that the scholars have different opinions regarding its legal status, there are those who allow it but some who forbid it. This treatment is part of the efforts of MaqÄá¹£id al-syarÄ«’ah as a guide in achieving benefit in human life. The application of maqÄá¹£id al-syarÄ«’ah as a whole in every aspect of people’s daily lives, will have an impact on ensuring the welfare of the people as a result of maintaining important aspects of life. The implications of this research when adopting leech therapy as a form of treatment that can treat various types of diseases must be based on expert advice to obtain maximum results.